Antifungal Activity of Ethanol Extract of Stem Bark And Fruit Flesh of Baccaurea Lanceolata Against Fungi Causing Skin Infections - Media Sasmita; Putut Marwoto; Sunyoto Eko Nugroho; Woro Sumarni (Postgraduate, University of Mataram, 2025)
Indonesia has a diversity of medicinal plants that are used by the community to treat various diseases. Indonesian people often experience skin problems caused by fungi. The high number of cases of fungal diseases is due to the high air humidity in the tropics, thus supporting the growth of fungi that cause skin infections. This study examines the phytochemical content and antifungal activity of Baccaurea lanceolata (lempaung) plants. The parts of lempaung used as samples are the stem bark and fruit flesh. Samples were taken in Bioa Sengok Village, Rimbo Pengadang District, Lebong Regency. Antifungal testing was conducted at the Chemistry Education Laboratory and Microbiology Laboratory of Bengkulu University (UNIB) from January to June 2022. Antifungal activity testing uses the disc diffusion method by immersing the disc into the ethanol extract of lempaung. The test fungi used were C. albicans, M. furfur, and T. mentagrophytes. The results of phytochemical tests showed that the stem bark and fruit flesh samples of lempaung contained alkaloids, flavonoids, tannins, saponins, steroids, and terpenoids. The antifungal activity test results showed that the samples had inhibition against C. albicans, M. furfur, and T. mentagrophytes.